Recent Advances in the Study of the Host-Fungus Interaction - Attila Gacser (Frontiers Research Topics, 2017)
Fungal infections represent nowadays a significant burden on the healthcare system of most of the countries, and are among the infections with the highest mortality rates. This has fostered the study of the interaction of these organisms with the human host. The outer most layer of a fungal cell is the cell wall, and together with the secreted components into the extracellular compartment, are the first lines of contact with the host cells. This interaction is critical for tissue adhesion, colonization and damage. In addition, these fungal extracellular components will define the outcome of the interaction with the host immune cells, leading either to the establishment of a protective antifungal immune response or to an immune-evasive mechanism by the fungal cell. On the other hand, our immune system has effectively evolved to deal with fungal pathogens, developing strategies for cell eradication, burden control, or antigen presentation from the innate branch to the adaptive immune response. Here, we provide a series of comprehensive review papers dealing with both aspect of the interaction fungus-immune cells: the role of virulence factors and cell wall components during such interaction, and the recent advances in the study of cellular receptors in the establishment of a protective anti-fungal immune response.